2024
DOI: 10.1128/jb.00239-23
|View full text |Cite
|
Sign up to set email alerts
|

Rapid turnover and short-term blooms of Escherichia coli in the human gut

Na Han,
Xianhui Peng,
Tingting Zhang
et al.

Abstract: Escherichia coli (E. coli ) is a common microorganism that is widely present in the environment and closely related to human health. The extent of E. coli presence in the human gut has been a subject of ongoing debate. Through whole-genome shotgun metagenomic sequencing, our study revealed that E. coli exists in the human body at a low abundance (average abundance 1.21%), with occasional short-term bursts leading to temporary increases in abundance, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 32 publications
0
1
1
Order By: Relevance
“…The 5-year longitudinal study revealed that Prevotella copri (Segatella copri) was consistently present in samples from P6 (March 2017 to November 2018), with genomic analysis indicating the same strain, without a turnover at the strain level. This finding is in contradiction with our previous finding based on Escherichia coli ( Han et al, 2024 ), as this species experiences a rapid monthly turnover rate (87.5% within a month), whereas Prevotella persists in the gut for a longer duration. We refer to Escherichia coli and other rapidly turning over bacteria, similar to it, as transient gut microbes.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…The 5-year longitudinal study revealed that Prevotella copri (Segatella copri) was consistently present in samples from P6 (March 2017 to November 2018), with genomic analysis indicating the same strain, without a turnover at the strain level. This finding is in contradiction with our previous finding based on Escherichia coli ( Han et al, 2024 ), as this species experiences a rapid monthly turnover rate (87.5% within a month), whereas Prevotella persists in the gut for a longer duration. We refer to Escherichia coli and other rapidly turning over bacteria, similar to it, as transient gut microbes.…”
Section: Discussioncontrasting
confidence: 99%
“…In the original classification framework, the longitudinal study of up to 5 years demonstrated short-term blooms or decreases in the abundance of Prevotella over time ( Figures 1C , 2A ). Short-term blooms, defined as instances where the abundance of Prevotella exceeded 5 times the individual’s average abundance, and short-term decreases, defined as abundance dropping to more than 5 times lower than the previous time point ( Zhang et al, 2022 ; Han et al, 2024 ), were observed. These fluctuations were recorded at 17 time points over the 5 years and were distributed among 7 individuals ( Supplementary Figure S1 ).…”
Section: Resultsmentioning
confidence: 99%